2014
DOI: 10.1155/2014/531087
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Esmolol Improves Coronary Artery Remodeling in Spontaneously Hypertensive Rats through Increased Nitric Oxide Bioavailability and Superoxide Dismutase Activity

Abstract: The aim of this study was to assess the effects of short-term esmolol therapy on coronary artery structure and function and plasma oxidative stress in spontaneously hypertensive rats (SHR). For this purpose, 14-month-old male SHR were treated for 48 hours with esmolol (SHR-E, 300 μg/kg/min). Age-matched untreated male SHR and Wistar Kyoto rats (WKY) were used as hypertensive and normotensive controls, respectively. At the end of intervention we performed a histological study to analyze coronary artery wall wid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…In a previous study, our group has demonstrated that, compared with SHR, plasma superoxide anion scavenging activity (including superoxide dismutase) was more pronounced in SHR-E and this was associated with an improvement in nitric oxide availability measured as nitrites/nitrates [ 37 ]. In the present study, short-term administration of esmolol restored catalase activity to the level detected in WKY controls.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, our group has demonstrated that, compared with SHR, plasma superoxide anion scavenging activity (including superoxide dismutase) was more pronounced in SHR-E and this was associated with an improvement in nitric oxide availability measured as nitrites/nitrates [ 37 ]. In the present study, short-term administration of esmolol restored catalase activity to the level detected in WKY controls.…”
Section: Discussionmentioning
confidence: 99%
“…septal coronary artery) or different methods of assessing vascular structure- histology (50, 51) vs . pressure myograph (52, 53). Thus, for future studies, it is imperative to differentiate and understand the differences between the coronary macrovascular (e.g.…”
Section: Coronary Microvascular Remodeling- What Are the Potential Kementioning
confidence: 99%
“…Additionally, asymmetric dimethylarginine (ADMA) – an endogenous inhibitor of NO- was increased in hypertensive animals and associated with aortic and coronary microvascular remodeling (53, 61). The decrease in ADMA was associated with attenuation of vascular remodeling of aorta and coronary artery, through an increase in NO bioavailability and superoxide dismutase (SOD) activity (52, 53, 61). …”
Section: Nitric Oxidementioning
confidence: 99%
“…This effect is particularly obvious in arterial grafts and is of interest for RA grafts, since this conduit is notorious for its susceptibility to vasospasms. The possible mechanism of this acute vasodilatory effect is nitric oxide (NO)-dependent vasodilatation as explained by Arnalich-Montiel et al, who demonstrated that esmolol induces acetylcholine-mediated NO-dependent vasodilatation in the coronaries of hypertensive rats (15). Similarly, in an in vivo human study of coronary arteries, esmolol infusion was shown to increase the minimal luminal diameter and decrease the endothelial shear stress in patients with moderate coronary stenosis (16).…”
Section: Discussionmentioning
confidence: 97%